Investigation of Residue Levels in Urine and Tissues of Rats That Treated Pentachlorophenol - O. ARSLAN, Seyfullah; OZAN, Kemal; UZUNOREN, Nuray (Annals of Medical Research, 2021)
None
Keywords: s : Pentachlorophenol, rats, dermal absorption, residue, urine, tissues, leather.